Dimensi Psikologis dalam Pendidikan Agama Islam: Membangun Keseimbangan Mental dan Spiritual - Zakiah Nasution (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the psychological dimensions of Islamic Religious Education (IRE) as an effort to build students’ mental and spiritual balance. The research employed a qualitative approach through library research, analyzing primary and secondary sources such as Qur’anic exegesis, Hadith, and relevant scholarly works. The findings reveal that IRE plays a strategic role in fostering mental health through habitual worship, the internalization of moral values. Furthermore, spirituality serves as the foundation of psychological well-being, safeguarding the purity of the heart and strengthening personality, as reflected in the Prophet’s Hadith on the centrality of the heart in determining human goodness. The study also highlights that IRE significantly contributes to building students’ resilience by reinforcing faith, instilling reliance on God (tawakkul), and drawing lessons from prophetic narratives. These aspects are crucial in helping young generations cope with identity crises, academic pressure, and the challenges of globalization. The integration of psychological and spiritual aspects within IRE learning processes is proven to produce students who are not only intellectually competent but also emotionally stable and spiritually strong.